2019
DOI: 10.1373/clinchem.2018.288332
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Men and Women in Mortality and the Health Dimensions of the Morbidity Process

Abstract: BACKGROUND: Do men have worse health than women? This question is addressed by examining sex differences in mortality and the health dimensions of the morbidity process that characterize health change with age. We also discuss health differences across historical time and between countries. CONTENT: Results from national-level surveys and data systems are used to identify male/female differences in mortality rates, prevalence of diseases, physical functioning, and indicators of physiological status. Male/fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
184
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(203 citation statements)
references
References 31 publications
14
184
1
4
Order By: Relevance
“…Although some papers state that females seldom follow these recommendations in comparison to males, the mortality rate from CVD is higher in males, especially in younger age [40]. This may be caused by the protective effect of the estrogens [39,40] and the sex chromosome of females [41,42]. If the consumption of high dietary CML is considered as an unhealthy diet, then the present study supports the statement above, by showing that ethnicity, level of education, intake of fat and intake of energy, are related to dCML and are further associated with WC, as one of the CVD risk factors, while only ethnicity is related to dCML and associated with BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Although some papers state that females seldom follow these recommendations in comparison to males, the mortality rate from CVD is higher in males, especially in younger age [40]. This may be caused by the protective effect of the estrogens [39,40] and the sex chromosome of females [41,42]. If the consumption of high dietary CML is considered as an unhealthy diet, then the present study supports the statement above, by showing that ethnicity, level of education, intake of fat and intake of energy, are related to dCML and are further associated with WC, as one of the CVD risk factors, while only ethnicity is related to dCML and associated with BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis highlights the importance of looking at the randomness of the mortality process and reveals important similarities between the distribution of lifespans of females and males. Due to a mixture of cultural, social, epidemiological and biological factors, males tend to die earlier, on average, compared to females (Crimmins et al, 2019;Rogers et al, 2010). Still, we found that in almost all points in time, between one and two men out of four outlived a randomly paired woman.…”
Section: Discussionmentioning
confidence: 99%
“…The female survival advantage has been observed over time across many human populations and is rooted in a complex combination of biological and behavioral factors (Austad & Fischer, 2016;Crimmins et al, 2019;Gjonça et al, 2005;Preston & Wang, 2006;Rogers et al, 2010). Females have been found to have longer survival and lower death rates than men in most modern populations (Austad & Fischer, 2016;Barford et al, 2006;Beltran-Sanchez et al, 2015;Gjonça et al, 2005;Luy & Gast, 2014) and even under extreme mortality conditions (Zarulli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Women also tend to suffer from a higher number of chronic diseases than men do, which is followed by their more frequent need for medical care. Women are believed to take on the role of patient faster and adapt to this situation better than men [18,19].…”
Section: Discussionmentioning
confidence: 99%